SAT0305 Interstitial Lung Disease (ILD) in Patients with Anti-Jo-1 Syndrome (AJS): A Descriptive Analysis. (10th June 2014) - Alhaddad, B.; O'Rourke, C.; Alalwani, M.; Zraik, B.; Yadav, R.; Chatterjee, S.
Abstract : Objectives: To evaluate the patterns, severity and prognostic parameters of ILD in AJS. Methods: We identified 51 anti-Jo-1 patients with ILD between 2003 and 2012. Clinical and laboratory data were obtained along with PFTs and pattern/scoring of thoracic HRCT scans based on Ooi scoring system (inflammation and fibrosis indices) (1). Progression of ILD was defined as follows: a decrease in DLCO and/or FVC (first to last reported) by >15%, an increase in fibrosis index or total HRCT score of ≥2, and death from respiratory failure. Results: Out of 51 patients; 20 were males and 15 had dermatomyositis. Median age at onset was 47 years, mean follow up duration was 6.6 years; 20% had ILD prior to AJS diagnosis. Arthritis, mechanic's hands, Raynaud phenomenon and fever were reported in 88%, 37%, 31%, and 23% respectively. Four patients had cancer: lung (1), prostate and gallbladder (1) and lymphoma (2). At diagnosis 3 patients had UIP, 13 (25%) had organizing pneumonia (3 with NSIP, 5 developed NSIP later); 36 (70%) had NSIP: 22 fibrotic, 2 mixed and 12 cellular; 75% of cellular NSIP became fibrotic on subsequent imaging. Mean DLCO and FVC at diagnosis were 58.9% and 67% respectively. Median initial inflammation and fibrosis indices at diagnosis were 5.6, 1.16 and at last follow up 4.8, 2.1 respectively. Among 45 patients with available follow up data; 17 had worsening ILD (39%) and 5 (11%) died of respiratory failure. Lower DLCO at diagnosis was a predictor of disease progression [50 vs. 65% (p=0.0290)]. All UIP patients progressed during follow up. Only 7 patients had a late diagnosis of ILD (≥3 years after onset of AJS). Of those; 5 (70%) had a DLCO ≤50% compared to 25% in those with early diagnosis. SSA positivity was detected in 53%; lower initial (53% vs. 62%) and last (56% vs. 67%) DLCO as well as higher fibrosis score at last follow up [3.5 vs. 0.9 (p=0.089)] were observed in SSA negative group. These differences did not reach statistical significance. Interestingly; 6 of 7 patients who died were SSA negative. Nine patients who developed pulmonary hypertension had higher median disease duration (10 years) and CT score (12.5) and all of them had DLCO ≤50%. Esophageal disease other than dysphagia was detected in 43% [GERD (33%), abnormal manometry or gastric emptying (15%) and dilatation on chest CT (10%)]. Esophageal disease had a trend towards lower DLCO at diagnosis [53 vs. 62% (p=0.084)], higher fibrosis score [2.7 vs. 1.6 (p=0.089)] and higher %change of total CT score [1.1 vs. -0.7 (p=0.007)]. Conclusions: Lower DLCO at diagnosis was associated with progression of ILD. The lower DLCO observed in late onset ILD may suggest silent disease and re-emphasize the rule of screening for ILD in AJS. In contrast with previous studies; SSA co-positivity was not associated with adverse outcome. Esophageal disease seemed to be prevalent in anti-Jo-1 patients with ILD and may predict worse fibrosis. The association of malignancy in AJS was not significant. References: Ooi et al; Interstitial lung disease in systemic sclerosis. Acta Radiol. 2003 May;44(3):258-64. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3984